2014
DOI: 10.3389/fncel.2014.00276
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic proteins and receptors defects in autism spectrum disorders

Abstract: Recent studies have found that hundreds of genetic variants, including common and rare variants, rare and de novo mutations, and common polymorphisms contribute to the occurrence of autism spectrum disorders (ASDs). The mutations in a number of genes such as neurexin, neuroligin, postsynaptic density protein 95, SH3, and multiple ankyrin repeat domains 3 (SHANK3), synapsin, gephyrin, cadherin, and protocadherin, thousand-and-one-amino acid 2 kinase, and contactin, have been shown to play important roles in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 139 publications
(165 reference statements)
3
91
0
Order By: Relevance
“…MiR-873-5p binds to key genes for synapse formation and function including all three SHANK family members (SHANK1, SHANK2 and SHANK3), three Neuroligin family members (NLGN2, NLGN3 and NLGN4X), Discs Large MAGUK Scaffold Protein 4 (DLG4 also known as PSD95), and two DLG associated proteins (DLGAP3 and DLGAP4), which have been linked to ASD by multiple studies [47,76,77] (Fig. 3e, Supplementary Table 6).…”
Section: Convergence Of the Rare Regulatory And The Proteincoding Varmentioning
confidence: 99%
“…MiR-873-5p binds to key genes for synapse formation and function including all three SHANK family members (SHANK1, SHANK2 and SHANK3), three Neuroligin family members (NLGN2, NLGN3 and NLGN4X), Discs Large MAGUK Scaffold Protein 4 (DLG4 also known as PSD95), and two DLG associated proteins (DLGAP3 and DLGAP4), which have been linked to ASD by multiple studies [47,76,77] (Fig. 3e, Supplementary Table 6).…”
Section: Convergence Of the Rare Regulatory And The Proteincoding Varmentioning
confidence: 99%
“…49,[52][53][54][55] A structure located in glutamatergic synapses that has been associated with both disorders is the postsynaptic density (PSD). 50,[56][57][58][59][60][61] For example, Bayés and colleagues found that mutations in 199 human PSD genes were involved in more than 200 diseases, half being nervous-system disorders. 61 That study suggested that impairments in PSD proteins might underlie psychiatric disorders and their associated cognitive, behavioural and clinical phenotypes, but no systematic review based on this hypothesis has integrated the molecular data generated across studies in the last decade.…”
Section: J Psychiatry Neurosci 2018;43(4)mentioning
confidence: 99%
“…25 ). Another important member of the neurexin family of proteins includes contactin-associated protein-like 2 (CNTNAP2), which is involved in neuron-glia interactions and clustering K + channels in myelinated axons 26 . Neuroligins are synaptic cell adhesion molecules that are enriched in postsynaptic membranes where they may recruit receptors, channels, and signal-transduction molecules 27 .…”
Section: Role Of the Cell Adhesion Molecules In Synapse Formationmentioning
confidence: 99%
“…Shank1-3 are synaptic scaffolding proteins that interact with a variety of membrane and cytoplasmic proteins. These proteins bind to neurexin-neuroligin complexes at postsynaptic excitatory glutamatergic synapses 26 . Specific positioning of Shank proteins at the postsynaptic sites of excitatory synapses suggests a role for this protein family in the organization of cytoskeletal/signaling complexes at specialized cell junctions 31 .…”
Section: Role Of the Scaffolding Proteins In Synapse Formationmentioning
confidence: 99%
See 1 more Smart Citation